Doxorubicin induces measurable vascular toxicity: assessment in a clinical and preclinical study. (10th June 2022) - Bosman, M; Boen, H; Franssen, C; Kruger, DN; Neutel, CHG; Favere, K; Van Asbroeck, B; Goovaerts, I; De Meyer, GRY; Van Craenenbroeck, EM; Guns, PJDF
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Fund for Scientific Research (FWO) Flanders INSPIRE project (H2020-MSCA-ITN program) Background: The chemotherapeutic doxorubicin (DOX) is frequently used to treat a wide variety of cancers, but the cardiotoxic side effects limits its clinical use in some patients. Additionally, DOX contributes to vascular toxicity, which may be an early manifestation of DOX-associated toxicity. Therefore, there is an interest to evaluate vascular function in patients receiving DOX-based treatment regimens. Purpose: We aimed to assess arterial stiffness and endothelial dysfunction as potential markers of vascular toxicity in both DOX-treated cancer patients and a murine model. Methods: Female breast cancer patients with a need for adjuvant or neoadjuvant DOX-based treatment were prospectively included. Chemotherapeutic regimen consisted of 12 weekly cycles of taxane treatment, followed by 4 cycles of DOX (and cyclophosphamide) treatment. Vascular function (endothelial function (FMD and RHI), arterial stiffness (Aix and cfPWV) and cardiac function (LVEF, hsTnI, NT-proBNP) were performed at baseline (T1), after completion of taxane treatment (T2) and after completion of DOX treatment (T3). In addition to the clinical study, male C57Bl6/J mice were intraperitoneally injected with 2 mg /kg (low dose) or 4 mg/kg DOX (high dose) once per week for 6 weeks. Arterial stiffness was assessed in vivo by measuring abdominal aorta pulse wave velocity (aaPWV) by high-frequency ultrasound imaging combined with ex vivo vascular function evaluation. Results: Twenty patients (mean age 51.2 +/- 10.1 yrs) treated with DOX were included. After DOX treatment (T3 vs T2), left ventricular ejection fraction (LVEF) was decreased, while hsTnI and NT-proBNP levels were increased, indicating cardiotoxicity (Table 1). Likewise, LVEF was reduced in DOX-treated mice after 3 weeks, which persisted until the end of the treatment (6 weeks). In patients, RHI was impaired at T2 and T3 compared to T1, which indicates progressive endothelial dysfunction during treatment (Table 1). Consistent with these findings, DOX treatment in mice resulted in endothelial dysfunction, as evidenced by a lower basal nitric oxide (NO) index and reduced acetylcholine-induced endothelium-dependent vasorelaxation (Figure 1B & 1C). Finally, cfPWV was decreased at T2 and T3 compared to T1, even after correction for BP, suggesting rather an improvement of arterial stiffness (Table 1). Although DOX treatment in mice resulted in a similar trend towards lower aaPWV at the end of treatment (6 weeks), we observed an initial increase in aaPWV after 2 weeks (Figure 1A). Conclusion: Collectively, these findings suggest that, apart from cardiotoxicity, DOX treatment results in early and consistent endothelial dysfunction, while evaluation of arterial stiffness may be time-sensitive. Hence, endothelial dysfunction may be a more reliable and sensitive marker than arterial stiffness to evaluate DOX-induced vascular toxicity in patients.